2014
DOI: 10.1007/s13726-014-0298-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted polymerization of methyl methacrylate using the reactive surfactant Hitenol BC10 in a semicontinuous heterophase process

Abstract: with R a ; however, monomer-starved conditions were favored at lower R a values. Very high-average molecular weights were observed (1.63 × 10 6 ≤ M w ≤ 2.34 × 10 6 g/ mol) which decreased when HBC10 concentration increased, and increased with R a . The corresponding polydispersity indexes (M w /M n ) were in the range of 1.55-2.30, showing relatively wide molar masses distributions. It was observed from differential scanning calorimetry that polymers with HBC10 presented two T g (123 and 178 °C) which was ascr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Since Rp is proportional to the number of polymer particles, when increasing the initial charge of Latemul ® PD-104, polymerization rate and the instantaneous conversion decreased. On the other hand, Vargas-Salazar et al [39] and Aguirreurreta et al, [40] observed a considerable reduction in the water absorption of the formed films using the polymers obtained in the presence of polymerizable surfactants compared to those with polymers from the synthesis with conventional surfactants, indicating the correct chemical incorporation of surfactant to polymer chains.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Since Rp is proportional to the number of polymer particles, when increasing the initial charge of Latemul ® PD-104, polymerization rate and the instantaneous conversion decreased. On the other hand, Vargas-Salazar et al [39] and Aguirreurreta et al, [40] observed a considerable reduction in the water absorption of the formed films using the polymers obtained in the presence of polymerizable surfactants compared to those with polymers from the synthesis with conventional surfactants, indicating the correct chemical incorporation of surfactant to polymer chains.…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that for some polymerizable surfactants, chain transfer reactions to the allyl double bond contribute to the reaction rate reduction. For example, Vargas-Salazar et al [39] polymerized MMA in the presence of HBC10 in a semicontinuous heterophase process assisted by ultrasound to obtain latexes with polymer contents of 24%. The conversions obtained for the polymerizations where the weight ratio of HBC10/MMA and the monomer addition rate were varied between 80% and 90%.…”
Section: Resultsmentioning
confidence: 99%
“…Mahmoudian et al used Triton X-100 as a surfactant for PMMA synthesis and reported sphere diameters between 100 and 300 nm [26]. Vargas-Salazar et al synthesized PMMA by ultrasound at 50 • C with Hitenol BC10 as a surfactant and reported average particle diameters between 39 and 63 nm [27]. However, the most frequently used surfactant for PMMA synthesis is sodium dodecyl sulfate (SDS), for which some reports have found particle diameters between 20 and 97 nm [28] and between 100 and 1000 nm [29].…”
Section: Introductionmentioning
confidence: 99%